Post-separation parenting arrangements and Development Outcomes for Infants & Children - Wells, Y; Smyth, B; Long, C; McIntosh, J (My University, 2010)
This synopsis summarises and integrates key findings from two recent Australian studies of outcomes for infants and older children in different post-separation parenting arrangements. Both studies were commissioned by the Australian Government Attorney-General’s Department. One was a panel study of high conflict parents who sought community-based mediation to resolve a parenting dispute, and included data collected over time from both parents and their children (n=131 families). The second study used data from national random samples of parents of 5,000 young infants and parents of 5,000 children aged 4–5 years, collected as part of the Longitudinal Study of Australian Children (see the ‘About the studies’ section below for more detailed information). We first outline an integrated summary of key findings from both studies, followed by details of each study, respective samples, study limitations, and thoughts on future research.
Keywords: Relationships -- Separation; Policy -- Parenting; Families; Families and relationships; Policy; Relationships; Families; Parenting; Separation; Families and relationships